If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 26x + 8 = 0 Reorder the terms: 8 + 15x + 26x = 0 Combine like terms: 15x + 26x = 41x 8 + 41x = 0 Solving 8 + 41x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 41x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 41x = 0 + -8 41x = 0 + -8 Combine like terms: 0 + -8 = -8 41x = -8 Divide each side by '41'. x = -0.1951219512 Simplifying x = -0.1951219512
| 3y+87=3+87y | | 9z+(40z+5)+5z=180 | | 54=36+a | | v+6=-8 | | 10=x-2 | | 2x+7(2x-12)=60 | | -3=-4+u | | ln(25x)-ln(x-1)=2 | | 3y+y-2y= | | 8(3x-1)=40 | | 5x+5=85-10x | | -7=9+v | | w-9=10 | | x+9=-20 | | 3=y+9 | | ln(1/x)+ln(2x^3)=ln(8) | | 6^4/4^3/3^6 | | 6=2+y | | 1-x=13 | | -5=5+2v | | -16=-8w+3(w+8) | | y=-1/6x+7 | | 9x+9-9=2 | | 4v+7=-17 | | -3(x-2)=-8x-44 | | F-9/-3=11-f/5 | | 1/2x^2-32=0 | | (x^2)/4+3x-8=0 | | -12=2x-6 | | 3x+2x-8+4=36 | | -11=-8v+5(v-4) | | 4x-2(x+2)=-8 |